Functional capacity: association with risk for falls, fear of falling and pain in the elderly - Alexandre de Andrade Nadu; Danila Cristina Paquier Sala; Carla de Lima Silva; Odete de Oliveira Monteiro; Paula Cristina Pereira da Costa; Meiry Fernanda Pinto Okuno (Rev Rene)
Objective: to associate functional capacity with the risk of falls, fear of falling, and pain in hospitalized elderly. Methods: cross-sectional study with 130 elderlies. The following scales were applied: Activities of Daily Living, Instrumental Activities of Daily Living, Morse Falls, Fear of Falling and Pain. The Kruskal-Wallis test was used to associate the categorical variables to the Daily Living Activities and Pain Scales and the Chi-square test to the Morse Falls. Spearman’s Correlation Coefficient was used to associate the continuous variables with the Fear of Falling Scale. Results: most of the elderlies were independent for basic and instrumental activities of daily living, had high risk for falls, little concern about the possibility of falling, and no pain. Those with higher risk for falls are those with more dependence and have more concern about falling. Conclusion: there was an association between functional capacity and the scales fear of falling and pain.